Factors associated with self-care behavior in patients with pre-dialysis or dialysis-dependent chronic kidney disease. - Jung-Won Ahn; Sun Mi Lee; Yon Hee Seo (PLoS ONE, 2022)
Self-care behavior plays a pivotal role in the management of chronic kidney disease. Improved self-care behavior in patients with chronic kidney disease is a key factor in health management and treatment adherence. This study aimed to evaluate the participants' general and medical condition-related characteristics, physiological indices and the level of health literacy affecting self-care behavior in patients with chronic kidney disease in South Korea. The data of 278 participants were analyzed using t-test, analysis of variance, correlation coefficient, and linear multiple regression analysis. There were significant differences in self-care behavior scores depending on participants' age and cohabitation status, employment, and smoking status as well as having dialysis due to end-stage kidney disease; number of comorbidities; levels of serum hemoglobin, calcium, and creatinine; and estimated glomerular filtration rate. The results of regression analysis revealed that not currently working, non-smoker, end-stage kidney disease, and positive response to the "actively managing my health" scale of the Health Literacy Questionnaire significantly affected self-care behavior in patients with chronic kidney disease, and the explanatory power of the model was 32.7%. Therefore, it is necessary to identify each patient's barriers or needs according to individual characteristics, such as age, cohabitation and employment status, and daily life circumstances, including smoking habits, comorbidities, social support, and level of health literacy to develop efficient support strategies for promoting adequate self-care behavior with CKD.